Edukacja dla zrównoważonego rozwoju w szkołach ponadgimnazjalnych - Elżbieta Buchcic (Studia Ecologiae et Bioethicae)
The aim of the realisation of the material is getting the results of carried on research concerning the fact of finding out to what level contents involving the balanced development during the educational activities was introduced, moreover, what influence of such issues on the creating the right attitudes towards the pro-ecological awareness of young people was.